Development of Puzzle Learning Media in Islamic Religious Education Subjects Class IV Elementary School - Andini, Andini; K., Nurdin; Sudirman, Sudirman; Rahman , Syamsiah (South Sulawesi Education Development (SSED), 2024)
This study uses the ADDIE model to develop learning media in puzzles for Islamic Religious Education class IV subjects at SDN 304 Mamara. The goal is to assess the stage of development, validity, and practicality of the media. The research method uses a qualitative and quantitative approach with data collection techniques through observation, interviews, questionnaires, and documentation. The study results showed that the puzzle learning media was categorized as